Integration of single-cell transcriptomes and chromatin landscapes reveals regulatory programs driving pharyngeal organ development - Magaletta, Margaret E.; Lobo, Macrina; Kernfeld, Eric M.; Aliee, Hananeh; Huey, Jack D.; Parsons, Teagan J.; Theis, Fabian J.; Maehr, Rene (Nature Communications, 2022)
Maldevelopment of the pharyngeal endoderm, an embryonic tissue critical for patterning of the pharyngeal region and ensuing organogenesis, ultimately contributes to several classes of human developmental syndromes and disorders. Such syndromes are characterized by a spectrum of phenotypes that currently cannot be fully explained by known mutations or genetic variants due to gaps in characterization of critical drivers of normal and dysfunctional development. Despite the disease-relevance of pharyngeal endoderm, we still lack a comprehensive and integrative view of the molecular basis and gene regulatory networks driving pharyngeal endoderm development. To close this gap, we apply transcriptomic and chromatin accessibility single-cell sequencing technologies to generate a multi-omic developmental resource spanning pharyngeal endoderm patterning to the emergence of organ-specific epithelia in the developing mouse embryo. We identify cell-type specific gene regulation, distill GRN models that define developing organ domains, and characterize the role of an immunodeficiency-associated forkhead box transcription factor.
CRIS-Team Scopus Importer:2023-03-08